Organizational Citizenship Behavior and Emotional Exhaustion: Examining the Role of Work-Family Conflict - Dian Ekowati; Syntya Kasman; Jovi Sulistiawan (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: The objectives of this study are, first, to examine the direct relationship between OCB-I/O to work-family conflict; second, to examine the relationship between OCB-I/O to emotional exhaustion; third, to examine the mediating effect of work-family conflict in the relationship between OCB-I/O to emotional exhaustion. Design/Methods/Approach: Quantitative method was employed in this study. Data was statistically managed using SEM-PLS. There were 235 respondents involved in the study comprising various employees across industries in Indonesia.  Findings: Overall, the study found support for all of its hypotheses. There is a positive correlation between engaging in extra-role behavior that benefits the organization, known as OCB-O, and emotional exhaustion. This means that when employees perform additional tasks beyond their formal obligations, it can result in emotional exhaustion. Similarly, a positive correlation exists between OCB-I, which involves discretionary actions towards colleagues, and emotional exhaustion. This behavior can also increase stress due to reduced resources for other tasks. Work-family conflict partially mediates the relationship between OCB-O and emotional exhaustion, suggesting that OCB-O can still influence emotional exhaustion even without going through the mediator of work-family conflict. The study also highlights the need for companies to monitor employee involvement in OCB behavior to ensure their resources are not depleted and evaluate employee well-being. Originality/Value: This research examines how OCB relates to various variables that previously have not been tested into one hypothetical model. This study has significant contributions to organizational behavior and human resources. While most studies focus on the positive effect of OCB, this study investigates the cost of being good citizens.  Practical/Policy implication: It offers significant implications for scholars and managers. Given the results, this study suggests that organizations need to monitor employees' engagement toward OCB so that employee can balance their contribution at the workplace and home. Through close monitoring, organizations can help employees maintain a work-life balance.